Effect of delta-p doping and i-region length scaling on ion/ioff in si nipin diode for selector application - Das, Bhaskar; Schulze, J.; Ganguly, Udayan (Springer Proceedings in Physics, 2019)
Higher Ion/Ioff and a low off state leakage is desirable for a selector diode for memory applications. Punch through based triangular barrier bidirectional Si NIPIN selector possess high on-off current ratio (>1 X 104) with a low off state leakage current. An Ion/Ioff >1X 106 at 1 V with an Ioff of 76 nA at 0.5 V, for NIPIN, has been demonstrated here, by scaling the i-region length and delta-p doping by simulation results which are calibrated with experimental results.
CRIS-Team Scopus Importer:2021-06-29